Enhanced Underground Communication: A Circularly Polarized Smart Antenna with Beam Steering for Improved Coverage - Muhammad Ahsan Mahboob; Muhammad Ahsan Ashraf; Iqra Atif; Hajime Ikeda; Glen T. Nwaila; Amer Masood; Jahanzeb Qureshi; Bekir Genc; Inamullah Khan; Bruce Mellado (Mining)
The underground mining industry faces significant challenges in maintaining reliable communication due to multipath fading and physical obstructions, leading to weak signals and dead spots. This study addresses these issues by proposing a smart antenna system with circular polarization and beam steering capabilities. The system utilizes a four-element square patch array and a Butler matrix for beamforming, enabling directional signal transmission. The antenna was designed and optimized using CST simulations. The experimental results demonstrate the antenna’s ability to steer beams in four directions, significantly reducing signal interference and improving coverage. The antenna achieved a bandwidth of 400 MHz (5.52–5.99 GHz) and a gain of up to 9.69 dBi, effectively mitigating polarization mismatches. The novelty of this study lies in the integration of circular polarization and beam steering into a compact, cost-effective system, specifically designed to enhance communication in underground mining environments. This solution improves both safety and operational efficiency by providing reliable communication in harsh conditions.